Social skills and life’s philosophy in pupils of secondary with and without participation in violent acts of Metropolitan Lima - Velásquez C., Carlos (2009)
The study was conducted in schools in Lima Metropolitana cones, with a sample of teens and preteens school male and female participants and non participants in violent acts. The instruments used were restructured factor: the Social Skills Scale (EHS) of Gismero. Leaving two factors: the ability to cope with adverse situations and ability to make appropriate requests, and the Philosophy of Life Questionnaire (FV) of Diaz-Guerrero. Leaving factors: Love adversus Power (FV1) and External Factor adversus Internal Factor (FV2). The result shows a low and positive relationship between variables. Regarding the status of students was only found significant differences in (FV1), where students do not aim their violent behavior by love, while the violent power. Preteens have a better management skills to make timely submissions as adolescents. Also their behavior is guided by love while adolescents for power. As to where students live only factor (FV1) differences, where they are predominant in the center of the capital is the power compared to other sectors.